Peran Bantuan Sosial dalam Pengentasan Kemiskinan Ekstrem di Jawa Timur Tahun 2020 - Akhmad Fatikhurrizqi; Bayu Dwi Kurniawan (Seminar Nasional Official Statistics, 2022)
East Java is the province with the largest number of poverty in Indonesia. It was recorded that in March 2020, the number of poverty in East Java was 4.109 million people with a percentage of 11.09 percent. In addition, East Java was selected in 7 priority provinces in efforts to eradicate extreme poverty. Extreme poverty is a condition where the level of community welfare is below the extreme poverty line of USD 1,9 PPP. This study aims to identify the characteristics and factors that influence extreme poverty in poor households in East Java in 2020. The method used is binary logistic regression with categories of extreme poor and poor. The results of this study indicate that the provision of Non-Cash Food Assistance (BPNT) has been directed at extreme poor households. Characteristics of extreme poor households tend not to rent a place to live. In addition, extreme poor households tend to have more families than poor households. These results can provide an overview of local governments in alleviating extreme poverty to zero by 2024 through optimizing the provision of assistance, especially BPNT.